2017
DOI: 10.1186/s12870-016-0954-6
|View full text |Cite
|
Sign up to set email alerts
|

SEP-class genes in Prunus mume and their likely role in floral organ development

Abstract: BackgroundFlower phylogenetics and genetically controlled development have been revolutionised during the last two decades. However, some of these evolutionary aspects are still debatable. MADS-box genes are known to play essential role in specifying the floral organogenesis and differentiation in numerous model plants like Petunia hybrida, Arabidopsis thaliana and Antirrhinum majus. SEPALLATA (SEP) genes, belonging to the MADS-box gene family, are members of the ABCDE and quartet models of floral organ develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…The results showed that CsMADS02 had 55.98-86.03% identity in deduced amino acid sequence with these SEP proteins, such as OsMADS1 in Oryza sativa (55.98% identity), SlCMB1 in Solanum lycopersicon (59.05% identity), GbSEP in Ginkgo biloba (59.91% identity), TaMADS1 in Triticum aestivum (68.78% identity), AtSEP3 in A. thaliana (78.33% identity), GmMADS28 in Glycine max (83.82% identity) and ZjMADS47 in Ziziphus jujuba (86.03% identity) ( Figure 2). In addition, the MADS domain and the K-box were relatively conserved, while the I and C regions were less conserved, which is in accordance with the results of a previous study [53]. Furthermore, two short conserved motifs (SEP motifs I and II) were present in the SEP proteins although the C-terminal regions were highly divergent (Figure 2).…”
Section: Sequence Alignment and Phylogenetic Relationships Between Cssupporting
confidence: 90%
“…The results showed that CsMADS02 had 55.98-86.03% identity in deduced amino acid sequence with these SEP proteins, such as OsMADS1 in Oryza sativa (55.98% identity), SlCMB1 in Solanum lycopersicon (59.05% identity), GbSEP in Ginkgo biloba (59.91% identity), TaMADS1 in Triticum aestivum (68.78% identity), AtSEP3 in A. thaliana (78.33% identity), GmMADS28 in Glycine max (83.82% identity) and ZjMADS47 in Ziziphus jujuba (86.03% identity) ( Figure 2). In addition, the MADS domain and the K-box were relatively conserved, while the I and C regions were less conserved, which is in accordance with the results of a previous study [53]. Furthermore, two short conserved motifs (SEP motifs I and II) were present in the SEP proteins although the C-terminal regions were highly divergent (Figure 2).…”
Section: Sequence Alignment and Phylogenetic Relationships Between Cssupporting
confidence: 90%
“…These sequences were cloned into pGBKT7 bait vector and pGADT7 prey vector at the EcoRI and BamHI sites, respectively, using an In-Fusion HD Cloning Kit System (Clonetech, USA). The Y2H assays were performed by former methods 42 . Each interaction analysis was performed three times.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from flower buds. Full-length cDNA of six PmDAMs and the plasmids of pMD TM 18-T- PmDAMs were extracted by previous methods ( Zhou et al, 2017 ). The primers and annealing temperatures of PCRs are shown in Supplementary Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…To clone these sequences into pGBKT7(bait) vectors and pGADT7 (prey) vectors (Clonetech, United States) at the Eco RI and Bam HI sites respectively, In-Fusion HD Cloning System (Clonetech, United States) was used. Yeast 2 hybrid assay was performed according to the previous method ( Zhou et al, 2017 ). The screenings for each interaction were applied in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation